Contribuciones para una ontoepistemología de la vivencia en educación - Maria Verónica Lopez Romorini; Claudia Liliana Perlo (EccoS – Revista Científica)
The aim of this paper is to contribute to the articulation of the concepts of cognition and life in educational practice, through the concept of experience. The theoretical corpus includes philosophical, psychological, biological, physical and neuroscientific basis, until rooting it in the concrete practice. Our ontoepistemological perspective is based on doing historical tour about the split of the concepts of doxa and episteme in the field of philosophy. Subsequently, it was developed the concept of experience. The relevance of this development is showed, as well as its scientific underpinnins, to propose an educational biocentric perspective, where the integration between knowledge and life is recovered. Finally it is presented the research results, from the setting in motion of this approach.